2016
DOI: 10.1016/j.jad.2016.01.051
|View full text |Cite
|
Sign up to set email alerts
|

A protocol for the Hamilton Rating Scale for Depression: Item scoring rules, Rater training, and outcome accuracy with data on its application in a clinical trial

Abstract: Background We present a fully articulated protocol for the Hamilton Rating Scale for Depression (HAM-D), including item scoring rules, rater training procedures, and a data management algorithm to increase accuracy of scores prior to outcome analyses. The latter involves identifying potentially inaccurate scores as interviews with discrepancies between two independent raters on the basis of either scores (≥ 5-point difference) or meeting threshold for depression recurrence status, a long-term treatment outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 18 publications
0
53
0
2
Order By: Relevance
“…Symptom severity was assessed via blind interviewer at pre-treatment, weekly during treatment (treatment weeks 1–5) and upon completing treatment (post-treatment). Rater’s made scoring decisions based on clearly defined item scoring rules (Rohan, Rough et al, 2016). In the parent trial, episode remission was defined as a pre- to post-treatment total SIGH-SAD score reduction of at least 50% in addition to a 21-item HAM-D score ≤ 7 and an 8-item atypical score ≤ 7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptom severity was assessed via blind interviewer at pre-treatment, weekly during treatment (treatment weeks 1–5) and upon completing treatment (post-treatment). Rater’s made scoring decisions based on clearly defined item scoring rules (Rohan, Rough et al, 2016). In the parent trial, episode remission was defined as a pre- to post-treatment total SIGH-SAD score reduction of at least 50% in addition to a 21-item HAM-D score ≤ 7 and an 8-item atypical score ≤ 7.…”
Section: Methodsmentioning
confidence: 99%
“…All SIGH-SAD interviews were audio recorded and independently rated by a second blinded rater. Discrepancies between raters were resolved using the procedures outlined in Rohan, Rough et al (2016). Intraclass correlations for inter-rater reliability ranged between 0.92 and 0.97 for pre-treatment, treatment weeks 1–5, and post-treatment (see Rohan, Rough et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…These two aspects were combined in the Structured Interview Guide for the Hamilton Depression Rating Scale – Seasonal Affective Disorder version (SIGH-SAD) 49. Rohan et al50 have recently presented a protocol and rules for the scoring of the HRSD and have reported high interrater reliability scores. A self-rating version of the SIGH-SAD rating scale is also available.…”
Section: Assessmentmentioning
confidence: 99%
“…A score of at least 19 on HDRS and a score of 4 or more on the 8 ATYP symptom score was indicative of SAD (Terman, Terman, & Rafferty, 1990). The inter-rater reliability trial of HDRS-SAD shows relatively low inter-rater discrepancy (5.6%), specially with items-""depressed mood", "work and activities", "middle insomnia", and "hypochondriasis" and atypical (SAD) items-"fatigability" and "Hypersomnia" (Rohan, Rough, Evans, Ho, Meyerhoff, Roberts, & Vacek, 2016). Given, some degree of discrepancy recorded with HDRS-SAD, the diagnosis of MDD and SAD will be made in conjunction with MINI, BDI-II and SPAQ that are shown to have high internal consistencies (Lecrubier et al, 1997;Magnusson, Friis, & Opjordsmoen, 1997;Storch et al, 2004).…”
Section: The Hamilton Depression Rating Scale -Seasonal Affective Dismentioning
confidence: 95%
“…Although these patients scored higher than cutoff on the atypical HDRS-SAD scale, a diagnosis of winter SAD could not be made as the peak depressive symptoms during winter with remission during the summer was not confirmed. Studies suggest inconsistencies with the HDRS scale (Uher, Farmer, Maier, Rietschel, Hauser, Marusic, Mors, Elkin, Williamson, Schmael, Henigsberg, Perez, Mendlewicz, Janzing, Zobel, Skibinska, Kozel, Stamp, Bajs, Placentino, Barreto, McGuffin, & Aitchison, 2008) and inter-rater discrepancies with HDRS-SAD with respect to the atypical SAD mood symptoms like "fatigability" and 'hypersomnia" (Rohan et al, 2016). It is unlikely that SAD participants have been included in this study as none of the participants had a self-reported history of SAD with worst mood during winter and complete remission during summer.…”
Section: Limitationsmentioning
confidence: 99%